Airbnb: Understanding the Concept, Recognizing the Values (Journal of Tourism and Hospitality Education, 2020)
Peer-to-peer (P2P) accommodation into the tourism market through a model of disruptive innovation is going to be very popular in the world. This has been coined as network hospitality led by Airbnb platform which will work as a mediator between the hosts and guests. Trust plays the major role for decision making to buy the shelter. The objective of studying this new area is to understand in better way through the help of secondary sources. Academic research is generally guided by the theories. Therefore, the researcher aimed to know which kind of concepts and models were applied by previous scholars. The study is confined to the Airbnb and Couchsurfing. For this study, the researcher has followed umbrella type of review research which will shed light on the knowledge of peer-to-peer accommodation and sharing economy.